ANALYSIS OF STUDENTS' DIFFICULTIES IN LEARNING ISLAMIC CULTURAL HISTORY AT MTS ZIA SALSABILA - Nurhaini Nurhaini; Zaini Dahlan (Jurnal Asy-Syukriyyah, 2026)
This research is motivated by the difficulties experienced by students in learning Islamic Cultural History (SKI) at MTs Zia Salsabila. Observations and interviews indicate that students frequently struggle to memorize the material, feel weary and bored during the learning process, and exhibit low concentration. Furthermore, students' low interest in reading SKI textbooks also affects their understanding of the subject matter. This study aims to analyze the forms of student difficulties, student comprehension, and the factors causing learning difficulties in Islamic Cultural History at MTs Zia Salsabila. This research employs a qualitative descriptive method with data collection techniques consisting of observation, interviews, and documentation. The results show that students' difficulties include easily forgetting the material, feelings of boredom and fatigue while studying, and low learning concentration. Factors contributing to these difficulties include limited instructional time, lack of parental support, and low reading interest. Therefore, efforts from both teachers and parents are necessary to increase students' motivation and interest in learning Islamic Cultural History.